2006
DOI: 10.1095/biolreprod.105.047084
|View full text |Cite
|
Sign up to set email alerts
|

Gestation Age-Related Increase in 50-kDa Rat Uterine Calcium-Independent Phospholipase A2 Expression Influences Uterine Sensitivity to Polychlorinated Biphenyl Stimulation1

Abstract: Phospholipase A2 (PLA2) enzymes catalyze the rate-limiting step in eicosanoid production by liberating arachidonic acid from membrane phospholipids. There is limited information regarding the expression pattern and activity of uterine PLA2 enzymes during pregnancy. Polychlorinated biphenyls (PCBs) are a group of persistent environmental toxicants previously associated with decreased gestation length that are capable of activating PLA2. The purpose of the present study was to determine whether uterine sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A decade passed by and Farrugia et al (1993) showed that type II PLA 2 is responsible for up to 80% of the total PLA 2 enzymatic activity present in placental tissues and that it represents the major component of PLA 2 activity in human fetal membranes at term (Aitken et al 1993). Recently, Brant et al (2006) showed a significant increase in rat uterine calciumindependent PLA 2 activity with the progression of labor. In the present work, we demonstrated a gestation-related increase of both the secretory and the cytosolic PLA 2 activities in the rat uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decade passed by and Farrugia et al (1993) showed that type II PLA 2 is responsible for up to 80% of the total PLA 2 enzymatic activity present in placental tissues and that it represents the major component of PLA 2 activity in human fetal membranes at term (Aitken et al 1993). Recently, Brant et al (2006) showed a significant increase in rat uterine calciumindependent PLA 2 activity with the progression of labor. In the present work, we demonstrated a gestation-related increase of both the secretory and the cytosolic PLA 2 activities in the rat uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Brant et al (2006) observed that sPLA 2 and cPLA 2 proteins are expressed in the rat uterus at mid (day 10) and late (day 20) pregnancy. Further evidence suggests that this enzyme could play a role in membrane remodeling but not in AA release (Murakami et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several splice variants of the enzyme are expressed yielding multiple molecular weight isoforms [25]. Recently, expression of a 50 kDa Group 6 enzyme in rat myometrium was associated with agonist-induced uterine contractions [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Further study revealed that the expression of genes (Pla2g2a, Pla2g5, Alox12e, and Cyp4a8) involved with arachidonic acid metabolism was increased in the Model group. Specifically, Pla2g2a and Pla2g5 genes, which are members of secretory phospholipase A2 family, can encode enzymes that liberate membrane phospholipids to produce free fatty acids such as AA (Brant et al, 2006). In addition, phospholipase A2 activity is increased under inflammation, causing elevated Alox12e gene expression, and the expression of pro-inflammatory cytokines is decreased after inhibition of Alox12e (Srikanth et al, 2018).…”
Section: Discussionmentioning
confidence: 99%